Tahapan Mendidik Anak Menurut Ali bin Abi Thalib dan Relevansinya di Era Modern - Khakim, Arif Rohman; Hidayah, Nurul (JoEMS (Journal of Education and Management Studies), 2023)
The development of quality young people is the central task of parents, to create quality people. For people who are Muslim, this step is inseparable from Islamic-based education. Nevertheless, in today's modern era, there are many negative influences that can stalk children. Therefore, the role of parents is very crucial in accompanying the development process of their children. One approach that can be applied is to take the example of the early generations of Islam, such as Ali Bin Abi Talib, to form a strong and enduring character. The objectives of this research include (1) Understanding what aspects of education are taught in the stages of children's education according to Ali Bin Abi Talib. (2) Considering the relevance of children's education according to Ali Bin Abi Talib in today's modern era. The method used in this study is a qualitative approach, more specifically, library research. Through this approach, research will describe, analyze, and clarify the stages of children's education according to Ali Bin Abi Talib, and then relate them to the relevance of the stages of children's education in the modern context. The results of this research will highlight that in the modern era, various rapid lifestyle changes can have a negative impact on the formation of a child's character, keeping him away from the spiritual and religious dimensions that have the potential to create a complete person. To overcome this, taking the example of the character possessed by the companion of the Prophet, Ali Bin Abi Talib, such as the sturdiness of faith, sense of responsibility, spirit of peace, courage, tolerance, and intelligence, can be one solution. Thus, the younger generation can grow as individuals who are balanced, have a deep religious values, while still being able to adapt in global dynamics.